Mitigating the prevalence and function of myeloid-derived suppressor cells by redirecting myeloid differentiation using a novel immune modulator. Issue 9 (23rd September 2022) - Oliver, Liliana; Alvarez, Rydell; Diaz, Raquel; Valdés, Anet; Colligan, Sean H; Nemeth, Michael J; Twum, Danielle Y F; Fernández, Audry; Fernández-Medina, Olivia; Carlson, Louise M; Yu, Han; Eng, Kevin H; et al.
Abstract : Background: Immune suppression is common in neoplasia and a major driver is tumor-induced myeloid dysfunction. Yet, overcoming such myeloid cell defects remains an untapped strategy to reverse suppression and improve host defense. Exposure of bone marrow progenitors to heightened levels of myeloid growth factors in cancer or following certain systemic treatments promote abnormal myelopoiesis characterized by the production of myeloid-derived suppressor cells (MDSCs) and a deficiency in antigen-presenting cell function. We previously showed that a novel immune modulator, termed 'very small size particle' (VSSP), attenuates MDSC function in tumor-bearing mice, which was accompanied by an increase in dendritic cells (DCs) suggesting that VSSP exhibits myeloid differentiating properties. Therefore, here, we addressed two unresolved aspects of the mechanism of action of this unique immunomodulatory agent: (1) does VSSP alter myelopoiesis in the bone marrow to redirect MDSC differentiation toward a monocyte/macrophage or DC fate? and (2) does VSSP mitigate the frequency and suppressive function of human tumor-induced MDSCs? Methods: To address the first question, we first used a murine model of granulocyte-colony stimulating factor-driven emergency myelopoiesis following chemotherapy-induced myeloablation, which skews myeloid output toward MDSCs, especially the polymorphonuclear (PMN)-MDSC subset. Following VSSP treatment, progenitors and their myeloid progeny were analyzed by immunophenotyping and MDSC function was evaluated by suppression assays. To strengthen rigor, we validated our findings in tumor-bearing mouse models. To address the second question, we conducted a clinical trial in patients with metastatic renal cell carcinoma, wherein 15 patients were treated with VSSP. Endpoints in this study included safety and impact on PMN-MDSC frequency and function. Results: We demonstrated that VSSP diminished PMN-MDSCs by shunting granulocyte-monocyte progenitor differentiation toward monocytes/macrophages and DCs with heightened expression of the myeloid-dependent transcription factors interferon regulatory factor-8 and PU.1. This skewing was at the expense of expansion of granulocytic progenitors and rendered the remaining MDSCs less suppressive. Importantly, these effects were also demonstrated in a clinical setting wherein VSSP monotherapy significantly reduced circulating PMN-MDSCs, and their suppressive function. Conclusions: Altogether, these data revealed VSSP as a novel regulator of myeloid biology that mitigates MDSCs in cancer patients and reinstates a more normal myeloid phenotype that potentially favors immune activation over immune suppression.